Structural and Mechanical Behaviour of Fe-30Ni Alloy Produced by a Powder Metallurgy Route. Issue 1 (2nd January 2017) - Singh, Neera; Banerjee, Sitashree; Parkash, Om; Kumar, Devendra
ABSTRACT: Alloy based materials are well known for their excellent mechanical, structural and electrochemical properties. The present paper reports the effect of sintering temperature on structural, mechanical and electrochemical behaviour of iron-nickel alloys. Iron-nickel alloys with 30 wt% nickel were prepared by powder metallurgy (P/M) route with a compaction load of 12 ton. The compact specimens were sintered at three different temperatures 1000°, 1200° and 1250°C for 1 h. Iron-nickel alloy formation was confirmed by X-ray diffraction studies. Hardness, wear and microstructural analysis were done with the help of Rockwell hardness tester, pin on disk wear testing machine and scanning electron microscope/ energy dispersive spectroscopy, respectively. Samples sintered at 1200°C showed better density, hardness, wear resistance and corrosion resistance than those of the other sintered specimens. In the present investigation, an effort was made to develop iron-nickel alloy for various advanced industrial applications. GRAPHICAL ABSTRACT: